Space-time power scheduling of MIMO links? fairness and QoS considerations - Rong, Yue; Hua, Y. (Institute of Electrical and Electronic Engineers, 2008)
Power control, beamforming and link scheduling are all important operations to improve the power-and-spectral efficiency of networks of multiple-input multiple-output (MIMO) wireless links. We call a joint optimization of the above operations the space-time power scheduling (STPS) scheme. The STPS scheme is formulated as joint optimization of the transmitter covariance matrices of all active MIMO links over all dimensions of space and time, which includes the dimension of frequency as a dual form of time. In this paper, we address the proportional fair (PF) and quality-of-service (QoS) issues of the STPS scheme, which are important for networks with asymmetric topology and/or asymmetric traffic demands. Both slow fading channels and fast fading channels are considered. We demonstrate that the PF-STPS scheme provides a very attractive tradeoff between sum capacity and rate distribution for asymmetric links. We also demonstrate that the QoS-STPS scheme has a much higher power-and-spectral efficiency than the previously existing QoS based scheme that do not exploit the temporal freedom. Efficient optimization algorithms for both PF-STPS and QoS-STPS are provided. The STPS scheme is a centralized cooperative scheme which requires a scheduler. For ad hoc networks, this scheduler can be elected adaptively among eligible nodes in the network.